2008
DOI: 10.1108/14635770810915904
|View full text |Cite
|
Sign up to set email alerts
|

Provider‐perceived dimensions of total quality management in healthcare

Abstract: PurposeThe purpose of this paper is to highlight key dimensions of provider‐perceived total quality management (TQM) in the healthcare sector in India. Further, the impact of the dimensions of provider perceived TQM on hospital performance is examined.Design/methodology/approachA questionnaire has been developed based on an extensive literature review of research in service quality and based on responses of the pilot survey among medical professionals. The instrument thus developed has been examined for its ps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
66
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(68 citation statements)
references
References 53 publications
2
66
0
Order By: Relevance
“…Goldstein et al (2002) in their study regarding hospital performance measures, they demonstrated that four measures are associated to hospital performance, the clinical measures such as adjusted length of patient stay in the hospital and adjusted mortality rate, secondly the financial measures such as operating cost and operating margin. In this regard performance measurement is an essential tool for evaluating overall healthcare service quality which should be practiced in every department of the hospital because it reflects the overall level of service quality (Duggirala et al, 2008). In order to be in line with all other service providing firms, all awards frameworks for service quality such as the Malcolm Baldrige National Quality Award (MBNQA), the ISO 9000 model, and the European Foundation for Quality Management (EFQM) use by healthcare units as a means of measuring hospital performance in achieving customers' satisfaction and retention (Lai, 2003).…”
Section: Hospital Performancementioning
confidence: 99%
“…Goldstein et al (2002) in their study regarding hospital performance measures, they demonstrated that four measures are associated to hospital performance, the clinical measures such as adjusted length of patient stay in the hospital and adjusted mortality rate, secondly the financial measures such as operating cost and operating margin. In this regard performance measurement is an essential tool for evaluating overall healthcare service quality which should be practiced in every department of the hospital because it reflects the overall level of service quality (Duggirala et al, 2008). In order to be in line with all other service providing firms, all awards frameworks for service quality such as the Malcolm Baldrige National Quality Award (MBNQA), the ISO 9000 model, and the European Foundation for Quality Management (EFQM) use by healthcare units as a means of measuring hospital performance in achieving customers' satisfaction and retention (Lai, 2003).…”
Section: Hospital Performancementioning
confidence: 99%
“…On the basis of an extensive review of the literature on healthcare service quality, this study adopts the instrument of Duggirala et al . (, ) to measure critical dimensions of patient‐perceived healthcare quality. These dimensions are now explained in the following section.…”
Section: Introductionmentioning
confidence: 99%
“…Duggirala et al . (, ) reviewed the critical dimensions of patient‐perceived healthcare quality dimensions and developed an instrument measuring the patient's viewpoint on healthcare quality. The following are the dimensions of patient‐perceived TQS in healthcare by Duggirala et al .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations